The impact of education on legislative responsiveness in three field experiments - Neiman, Jayme (Cogent social sciences, 2017)
Three field experiments were used to investigate whether a constituent’s education level influences state legislators’ responsiveness to their request for assistance. Legislators were sent emails that were randomly varied as to the education level of the writer. Results indicate that communication from constituents with lower education levels receive fewer replies. Two potential explanations for the variation in legislative response are explored—political party and the legislator’s own education level. Analysis suggests that neither of these variables account for the response differential to the email manipulations.